Upaya Meningkatkan Kualitas Pendidikan melalui Peran Kepala Sekolah - Abdulloh, Abdulloh (Studia Manageria, 2022)
The focus of this research is emphasized on the quality of education at SMK Muhammadiyah 7 Gondanglegi, which is about the principal's efforts to improve the quality of education.There are several arguments that form the basis of this research, first, this school is included one of the leading Vocational High Schools (SMK) in Malang Regency. Second, although this school is relatively new compared to other schools in Gondanglegis sub-district is able to provide quality, quantity, even facilities exceed other schools in Gondanglegi.And third, this school has issuing high quality graduates (outputs) where these graduates are now widely scattered in several colleges. There is a limitation of the problem in this study so that the problem formulation is concluded which was taken by researchers to conduct this research, namely (1) How is the effort of the head schools in improving the quality of education at Muhammadiyah 07 Gondanglegi Vocational High School (SMK) Malang (2) How is the success of the principal in improve the quality of education in Muhammadiyah Vocational High School (SMK) 07 Gondanglegi Malang (3) How is the success of the principal in improving the quality of education in Muhammadiyah 07 Vocational School (SMK) Gondanglegi Malang. The method used in this research is descriptive qualitative, namely one a type of research that aims to describe and understand certain phenomena.Method data collection used is by means of documentation and interviews.The findings of this study are (1) the principal's efforts to improve the quality of education which is done in many ways.(2) obstacles faced by school principals as well solutions / policies in improving the quality of education (3) The success of the principal in improving the quality of education, in this case the researcher reveals the success this by describing the achievements and reputations that were obtained and held by the SMK Muhammadiyah 07 Gondanglegi during the last four years in the leadership of Bpk H. Pahri, S.Ag., MM. Keywords: Education; quality; principal